The application of biological motion research: biometrics, sport, and the military - Steel, K.; Ellem, E.; Baxter, D. (Psychonomic Bulletin & Review, 2015)
The body of research that examines the perception of biological motion is extensive and explores the factors that are perceived from biological motion and how this information is processed. This research demonstrates that individuals are able to use relative (temporal and spatial) information from a person`s movement to recognize factors, including gender, age, deception, emotion, intention, and action. The research also demonstrates that movement presents idiosyncratic properties that allow individual discrimination, thus providing the basis for significant exploration in the domain of biometrics and social signal processing. Medical forensics, safety garments, and victim selection domains also have provided a history of research on the perception of biological motion applications; however, a number of additional domains present opportunities for application that have not been explored in depth. Therefore, the purpose of this paper is to present an overview of the current applications of biological motion-based research and to propose a number of areas where biological motion research, specific to recognition, could be applied in the future.